2015
DOI: 10.3329/ajmbr.v1i2.25618
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification and antibiogram profile of bacteria isolated from dental caries patients of Mymensingh district of Bangladesh

Abstract: This study was carried out for the evaluation of causative agents of dental plaques which leads to dental caries. A total of 76 samples collected from the dental caries patients of various age and sex were processed on different bacterial isolation media like Tryptose Soya Agar, Nutrient Agar, and MacConkey Agar. Total viable count of bacteria was ranged from 0.8×10 5 to 2.9×10 5 . Out of total 184 isolates bacterial species were Streptococcus mutans (28.80%), Streptococcus mitis (23.91%), Staphylococcus aureu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…This study's results corroborate those of [23], which found that the prevalence of dental caries was highest among those aged 31 to 40. Similar to the current study [24], revealed that the maximum prevalence (32.60%) of infection was established in the 26-35 age group, while the lowest prevalence (10.18%)…”
Section: Isolation and Identification Of Bacterial Isolatessupporting
confidence: 90%
See 1 more Smart Citation
“…This study's results corroborate those of [23], which found that the prevalence of dental caries was highest among those aged 31 to 40. Similar to the current study [24], revealed that the maximum prevalence (32.60%) of infection was established in the 26-35 age group, while the lowest prevalence (10.18%)…”
Section: Isolation and Identification Of Bacterial Isolatessupporting
confidence: 90%
“…It discovered that a more significant proportion of females (80%) were affected by dental caries, which is consistent with the current study's findings. The bacterial frequency based on isolates was more or less similar to the study of [13,24], which identified Almost all of the bacteria in this study are pathogenic, which can cause tooth decay. We noticed that most antibiotics were highly resistant, that's why it is challenging to control dental decay.…”
Section: Isolation and Identification Of Bacterial Isolatessupporting
confidence: 85%
“…Various species of the genus Streptococcus, Staphylococcus, Lactobacillus, Enterococcus, Corynebacterium, Veillonella and Bacteroids are predominant bacteria in the human oral cavity. Mutans group Streptococci (Streptococcus mutans and Streptococcus sobrinus), mittis group Streptococci (Streptococcus sanguinis, Streptococcus oralis, and Streptococcus gordonii) and Salivarius group (Streptococcus salivarius) are major constituents of human oral flora [8][9][10][11]. High levels of S. mutans and early colonization are considered key risk factors for the development of dental caries in both children and adults [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates the need to determine the microbial load or status of RTE foods to prevent foodborne diseases and promote health and well-being. In Bangladesh, some previous microbiological studies conducted to know respiratory bacterial agents from buffalo (Akter et al, 2018), bacterial load in dental caries (Borty et al, 2015), bacterial load of poultry meat (Hossain et al, 2015), bacteria from mobile phones of student (Hussein et al, 2020), bacteria isolated from table eggs (Islam et al, 2018), bacterial species isolated from milk (Munsi et al, 2016), bacterial pathogens from egg shell, egg yolk, feed and air samples (Parveen et al, 2017), bacterial loads in butter and cheese (Parvin et al, 2016), bacterial population of raw milk (Rana et al, 2021) and antibiotic sensitivity of bacteria in raw milk (Talukder and Ahmed 2016). A very few studies are conducted to assess the bacterial load and their antibiogram in RTE foods, however, this study is the first study from the current study location for assessing the bacterial load and their antibiogram in RTE foods.…”
Section: Introductionmentioning
confidence: 99%